PENERAPAN KURIKULUM 2013 DI SEKOLAH DASAR NEGERI 6 PALU - Nuritasari Nuritasari; Thalib Thalib; Karmawati Karmawati (IBTIDAI'Y DATOKARAMA: JURNAL PENDIDIKAN DASAR, 2020)
This research deals with the "Implementation of the 2013 Curriculum in Negeri 6 Primary School, Palu". The main issue of this research is how is the implementation of the 2013 Curriculum in SDN 6 Palu? And what are the obstacles faced by schools and their solutions in implementing the 2013 Curriculum at SDN 6 Palu? The purpose of this study was to determine the implementation of the 2013 Curriculum at SDN 6 Palu and to find out the constraints faced by schools and their solutions in implementing the 2013 Curriculum at SDN 6 Palu. This type of research is a descriptive study using a quantitative approach supported by a qualitative approach. Research subjects are all class teachers and school principals. Data collection techniques include questionnaires, interviews, and documentation. Questionnaire technique for collecting data regarding the application of the 2013 Curriculum which consists of aspects of RPP design, learning implementation, and assessment implementation. While the interview technique was carried out directly to obtain information about the constraints and solutions for implementing the 2013 Curriculum by expressing questions to the informants namely 5 class teachers as representatives and principals of SDN 6 Palu. The documentation technique is carried out to perpetuate the process of conducting research and taking a number of data/documents that support research. The results showed that 1) the implementation of the class teacher lesson plan is 70.33% with a good category, 2) the learning process that is 53.33% is in the poor category, 3) evaluation/assessment of learning which is 63.33% is in a good category. While the obstacles in the design of the lesson plan there are no obstacles, for the implementation of learning there are obstacles but can be overcome by every teacher, in the implementation of the assessment there are obstacles in terms of the time of the implementation of the assessment and solutions to overcome them also require attention from the government. The implication of the research is that it is expected that the writer as a holder of the preparation and application of the 2013 curriculum at SDN 6 Palu and as a reference and consideration for curriculum improvement in the future